(untitled) (Studia Prawnicze / The Legal Studies, 2018)
W artykule przedstawiono rozważania na temat przenikania się w systemie prawa instytucji prawa administracyjnego, konstytucyjnego i pracy. W ujęciu historycznym wskazano na kierunek i dynamikę zmian w obszarze prawa urzędniczego. Wskazano na pozaprawne czynniki wpływające na ustawodawcę, które powodują zaburzenie jasnego, teoretycznego podziału prawa na gałęzie prawa. Rozważania zilustrowano orzecznictwem sądów administracyjnych i powszechnych a także Trybunału Konstytucyjnego w zakresie interpretacji wybranych, kluczowych instytucji prawa urzędniczego, tj. zakresu podmiotowego służby cywilnej, zakresu pojęcia „administracja rządowa” i istoty postępowania kwalifikacyjnego w służbie cywilnej. The study discusses the interpenetration of administrative, constitutional and labor law institutions in the legal system. In historical terms, the direction and dynamics of changes in the area of civil service law have been indicated. Non-legal factors influencing legislators, which disrupt the clear, theoretical division of law into branches of law, have been indicated. The considerations are illustrated by the jurisprudence of the administrative and common courts as well as the Constitutional Tribunal, in the field of interpretation of selected key institutions of civil service law (the subjective scope of the civil service, the scope of the term ‘government administration’ and the essence of the qualification procedure in the civil service).